Examining the technologies and practices that can help SA mining industries meet carbon blueprint reductions - Lakhna, Adheesh (University of the Witwatersrand, Johannesburg, 2023)
Mining has always been regarded as a black sheep due to its legacies of environmental accidents, pollution, and safety incidents. However, for economies to grow, they need energy and energy requires metals to generate, transmit and store power. These metals are mostly sourced from mining and so as the world changes to cleaner and greener energy options, it is only fitting that mining equipment also becomes more environmentally friendly and keep up with the times. Heavy mining equipment such as ultra class dumptrucks and face shovels have 2-3MW diesel engines which can easily burn hundreds of litres of diesel per hour (Komatsu, 2022). Diesel has been the fuel of choice for many years due to its developed supply chains, ease of storage, high energy density and reliable engines. High fuel consumptions coupled with increasing fuel prices and deepening mines means that in addition to increasing expenses and pressure from environmental organisations, South African mines are becoming more and more carbon intensive. In December of 2015, at the 21st Conference of the Parties (COP21) to the United Nations Framework Convention on Climate Change (UNFCCC) held in Paris, an international treaty on climate change was adopted by 195 parties. This treaty also known as the Paris agreement was a landmark agreement since this was the first legally binding treaty aimed at fighting climate change (United Nations Climate Change, 2015). The Paris agreement covered many items but these are some of the most crucial ones; Long-term temperature goals with the aim of restricting global temperature increases to below 2 degrees Celsius or even further to 1.5 degrees Celsius; National Adaptation Plans which outlines plans and actions for different nations based on their needs and priorities; Finance, technology and capacity-building support that addresses developed countries providing financial assistance to less endowed countries for adaption and accelerating technology development
A research report submitted in partial fulfillment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: Technology; Practices; SA mining; Carbon; Reductions; UCTD; SDG-9: Industry, innovation and infrastructure